Community perceptions of natural supports and their approaches: A Canadian grounded theory study with Connections First - Jessica-Lynn A. Walsh; Kiran Pohar Manhas; Nikki Stephenson; Sheila W. McDonald; Scott B. Patten; Suzanne C. Tough (PLoS ONE, 2026)
Community-based informal reciprocal interactions (natural supports) enhance individual and community well-being. Like social connections, natural supports aim to establish supportive and healthy environments, but with a greater focus on local surroundings. This study explored natural support approaches within communities in an urban Canadian center. Employing grounded theory, purposive and theoretical sampling identified participants familiar with the community and its opportunities and activities, referred to as community champions. These champions were interviewed about their perceptions of resident connectivity and the key facilitators and barriers related to natural supports approaches in their communities. Themes and categories emerged, leading to the development of a theory. The overarching theory posited “ building a community’s capacity to transition from disconnected to naturally supportive: the need for connectors, assets, and action to empower residents”. Community connectors and assets facilitate natural support approaches within urban community settings. Limited access to space and challenges in recruiting and retaining volunteers were identified as barriers. The findings empower knowledge users, such as community planners, to invest in and promote community natural supports approaches to enhance resident and community well-being. Future directions for this study include the implementation and evaluation of natural support approaches within communities.